The Existence of Didactic Values in "Percy Jackson and the Olympians Lightning Thief” Novel by Rick Riordan - Hastuti Retno Kuspiyah; M. Andrey Saputra; Eka Agustina; Ferdianto (Channing : Journal of English Language Education and Literature, 2022)
This study aims to describe didactic values in the "Percy Jackson And The Olympians Lightning Thief" novel by Rick Riordan. This study employed a descriptive qualitative methodology. The method for gathering data in this study has several steps, namely novel identification, identification of unit analysis, data collection, and data categorization The data source for this research was Percy Jackson And The Olympians Lightning Thief novel by Rick Riordan. The Didactic values that were the focus of this research were Sharing, Responsibility, Empathy, and Helping Others. Based on the results of data analysis found didactic values as many as 26 data. The first number of findings, Sharing values were 6 (23%) findings. It was a value that focused on sharing activities that can be beneficial. Second, Responsible values with a total of 10 (39%) findings. It was a value that focused on being responsible in doing anything. Third, Empathy Values with a total of 6 (23%) findings. It was a value that focused on understanding what other people feel and think. And the Fourth is helping Other values with a total of 4 (15%) findings. It was a value that focused on helping each other. Thus, from this amount, it can be concluded that the novel Percy Jackson And The Olympians Lightning Thief by Rick Riordan found many didactic values with a total of 26 data findings and the most dominant Didactic values were found Responsible values with 10 data findings.